Oral microbiome, nutrition and their role in oral carcinogenesis - Arzmi, Mohd Hafiz (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2019)
A balanced oral microbiome is essential in maintaining a healthy oral cavity. Oral microbiome comprises of various microorganisms that belong to different kingdoms, including bacteria (bacteriome) and fungal (mycobiome). Multiple factors have been shown in oral carcinogenesis including alcohol consumption, tobacco smoking, betel nut chewing and microbial infections. Since the oral cavity comprises of various microbial kingdoms, thus, inter-kingdom interactions are suggested in promoting oral carcinogenesis. Dysbiosis, which is defined as imbalance inter-kingdom microbiome, alone may not cause oral carcinogenesis; thus, it is suggested that nutritional factor may also play a vital role in this disease development. A recent study has shown that sucrose consumption can induce the production of glucosyltransferases (gtfs) by Streptococcus mutans which lead to the increasing attachment of Candida albicans in polymicrobial biofilms form. The yeast has been reported to be potentially involved in oral carcinogenesis, particularly in the immunocompromised patient. This is due to the inflammation that is caused by candidal infection, which increases pro-inflammatory cytokines such as interleukin-6, interleukin-8 and interleukin-10, that have been linked to oral carcinogenesis. However, further study is needed to conform to the claim. In addition, over-consumption of alcoholic beverages has also been related to carcinogenesis which the ethanol has been reported to be converted into acetaldehyde by C. albicans using acetaldehyde dehydrogenases enzymes. In Malaysia, oral cancer has also been related to the consumption of cured and salted fish, which mostly consumed by the Chinese ethnics. However, its relationship to oral microbiome remains unclear. In conclusion, oral micro'biome and nutrition may have a role in oral carcinogenesis; however, further study is needed to elucidate the role of both factors in oral cancer development.